1997
DOI: 10.1111/j.1600-0404.1997.tb00097.x
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative study of daytime sleepiness induced by carbamazepine and add-on vigabatrin in epileptic patients

Abstract: Some sleepiness occurs in chronically CBZ-treated epileptic patients, which can be objectively measured by the MSLT, but it is not aggravated by add-on VGB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…Only one class III study in patients with focal epilepsy was identified in which the patients on chronic carbamazepine therapy were enrolled . Patients with poorly controlled seizures received vigabatrin as an adjunctive therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Only one class III study in patients with focal epilepsy was identified in which the patients on chronic carbamazepine therapy were enrolled . Patients with poorly controlled seizures received vigabatrin as an adjunctive therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Many drugs exert a stabilizing effect on sleep improving sleep quality, others aggravate sleep parameters, while dose-dependent effects have not been extensively evaluated, yet. 30,31 On the other hand, sleep alterations can influence epileptic activity, as sleep stages represent forms of varied neuronal synchronization. Non-REM (NREM) sleep is known to facilitate seizures onset and spread, while REM stage suppresses epileptic activity, as it consists a state of cortical desynchronization.…”
Section: Discussionmentioning
confidence: 99%
“…However, conflicting studies reported that CBZ did not influence the sleep of patients with epilepsy or disturbed it by increasing wake/sleep fragmentation, thus diminishing both SWS and REM sleep. Some researchers thought that these are merely initial effects that can be reversed by chronic treatment [ 135 , 136 , 140 , 141 ]. A similar agent is phenytoin (PHT), an AED that falls into the same group as CBZ.…”
Section: Sleep and Anticonvulsant Therapymentioning
confidence: 99%